Characterization of the complete chloroplast genome of Swertia souliei (Gentianaceae). Issue 2 (2nd April 2020) - Bi, Hao; Yang, Yanting; Hu, Quanjun; Ma, Yazhen
Abstract: The complete chloroplast genome sequence of Swertia souliei, an alpine annual herbaceous plant endemic to the Qinghai-Tibetan Plateau (QTP), is reported in this study. The plastome is 152, 804 bp in length, with one large single-copy region of 83, 195 bp, one small single-copy region of 18, 096 bp, and two inverted repeat (IR) regions of 25, 756 bp. It contains 130 genes, including 85 protein-coding, 8 ribosomal RNA, and 37 transfer RNA genes. Phylogenetic tree shows that this species is a sister to the clade containing S. leducii, S. verticillifolia, and S. mussotii . The complete chloroplast genome could provide significant insight for understanding the phylogenetic relationship of taxa within Gentianaceae.